Anti-nociceptive and sedative effects of romifidine, tramadol and their combination administered intravenously slowly in ponies. (March 2015) - Costa, Giovanna L; Cristarella, Santo; Quartuccio, Marco; Interlandi, Claudia
Abstract: Objective: To evaluate the anti-nociceptive and sedative effects of slow intravenous (IV) injection of tramadol, romifidine, or a combination of both drugs in ponies. Study design: Within-subject blinded. Animals: Twenty ponies (seven male, 13 female, weighing mean ± SD 268.0 ± 128 kg). Methods: On separate occasions, each pony received one of the following three treatments IV; romifidine 50 μg kg − (R) tramadol 3 mg kg −1 given over 15 minutes (T) or tramadol 3 mg kg −1 followed by romifidine 50 μg kg −1 (RT). Physiologic parameters and caecal borborygmi (CB) were measured and sedation and response to electrical stimulation of the coronary band assessed before and up to 120 minutes following drugs administration. Results were analyzed using the Friedman's test and 2 wayanova as relevant. Results: When compared to baseline, heart (HR, beats minute −1 ) and respiratory rates (fR, breaths minute −1 ) increased with treatment T (highest mean ± SD, HR 43 ± 1; fR 33 ± 2) and decreased with R (lowest HR 29 ± 1 and fR 10 ± 4) and RT (lowest HR 32 ± 1 and fR 9 ± 3). There were no changes in other measured physiological variables. The height of head from the ground was lower following treatments R and TR than T. There was slight ataxia with all three treatments. No excitatory behavioural effects were observed. The response to electrical stimulation was reduced for a prolonged period relative to baseline following all three treatments, the effect being significantly greatest with treatment RT. Conclusion: Tramadol combined with romifidine at the stated doses proved an effective sedative and anti-nociceptive combination in ponies, with no unacceptable behavioural or physiologic side effects. Clinical relevance: Slow controlled administration of tramadol should reduce the occurrence of adverse behavioural side effects.